2014
DOI: 10.1161/jaha.113.000544
|View full text |Cite
|
Sign up to set email alerts
|

“Not the ‘Grim Reaper Service’”: An Assessment of Provider Knowledge, Attitudes, and Perceptions Regarding Palliative Care Referral Barriers in Heart Failure

Abstract: BackgroundAlthough similar to cancer patients regarding symptom burden and prognosis, patients with heart failure (HF) tend to receive palliative care far less frequently. We sought to explore factors perceived by cardiology, primary care, and palliative care providers to impede palliative care referral for HF patients.Methods and ResultsWe conducted semistructured interviews regarding (1) perceived needs of patients with advanced HF; (2) knowledge, attitudes, and experiences with specialist palliative care; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
212
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(226 citation statements)
references
References 51 publications
8
212
0
6
Order By: Relevance
“…One of the most common misconceptions relating to palliative care within HF is the belief that the philosophy of palliative care is incompatible with that of aggressive management and this is perhaps the greatest challenge to ensuring the integration of a palliative care approach into HF management (Gott et al, 2011;Kavalieratos et al, 2014). This study confirmed this misconception with over three quarters of respondents believing, incorrectly, that the philosophy of palliative care was incompatible with that of aggressive treatment.…”
Section: Palliative Care Knowledgesupporting
confidence: 55%
See 1 more Smart Citation
“…One of the most common misconceptions relating to palliative care within HF is the belief that the philosophy of palliative care is incompatible with that of aggressive management and this is perhaps the greatest challenge to ensuring the integration of a palliative care approach into HF management (Gott et al, 2011;Kavalieratos et al, 2014). This study confirmed this misconception with over three quarters of respondents believing, incorrectly, that the philosophy of palliative care was incompatible with that of aggressive treatment.…”
Section: Palliative Care Knowledgesupporting
confidence: 55%
“…This study confirmed this misconception with over three quarters of respondents believing, incorrectly, that the philosophy of palliative care was incompatible with that of aggressive treatment. Kavalieratos et al (2014) also found that clinicians on the whole do not recognise that palliative care need not be prognosis dependent but can be provided alongside life prolonging treatment. There is no conflict between palliative care and active management approaches; one does not commence where the other ends.…”
Section: Palliative Care Knowledgementioning
confidence: 99%
“…When multidisciplinary HF providers were interviewed to assess knowledge, attitudes, and perceptions about palliative care, they reported limited palliative care knowledge, confused palliative and hospice care, and were uncertain about differences between standard HF therapy and palliative care. 285 A survey of HF nurses found that 67% felt it was a physician's role to initiate discussions about end-of-life care with patients, and 91% reported a need for more palliative training. 286 Additional barriers to the provision of palliative care services identified by healthcare providers included uncertainty about end of life because of its unpredictable trajectory, lack of need for end-of-life discussions in patients in New York Heart Association class II to III HF, and lack of time and resources to initiate discussions.…”
Section: Palliative Care Use and Perceptions In Cardiovascular Practicementioning
confidence: 99%
“…111 By determining patient and caregiver goals of care through skilled communication, treating distressing symptoms while coordinating care, providing practical support for patients and caregivers, and mobilizing community support and resources to ensure a secure and safe living environment, palliative care teams help meet patient and caregiver needs so that they can avoid unwanted and expensive crisis care. [112][113][114] Many large US hospitals now have palliative care services, but availability across settings is highly variable by region and by state. Only a small fraction of the patients and families who could benefit receive it.…”
Section: May 8 2018mentioning
confidence: 99%